1993
DOI: 10.1172/jci116275
|View full text |Cite
|
Sign up to set email alerts
|

Higher-affinity oligosaccharide ligands for E-selectin.

Abstract: A series of synthetic oligosaccharides based on sialyl Lewis x (sLex; and sialyl Lewis a (sLe'; Neu5Acca2-3Gall#1-31Fuca1-4jGlcNAc) was used to study the binding interactions of selectins. E-selectinimmunoglobulin fusion protein (E-selectin-Ig) bound to immobilized bovine serum albumin (BSA)-neoglycoproteins containing sLex or sLea in a Ca2"-dependent manner. Solutionphase sLex tetrasaccharide blocked this interaction by 50% at a concentration of 750±20 ,M (IC50). sLe' was more effective (IC50 = 220±20 ,uM), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
87
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(100 citation statements)
references
References 74 publications
11
87
2
Order By: Relevance
“…An obvious candidate to explain the L-and P-selectin-independent leukocyte rolling is E-selectin, the third member of the selectin family and a glycoprotein also postulated to induce leukocyte rolling (49). It is, however, unlikely that E-selectin participates in this rolling event since the leukocyte rolling in this study was abolished by fucoidin yet fucoidin has been shown not to bind to E-selectin (18,50). Although the identity of the fucoidin-sensitive pathway remains unknown, it is conceivable that fucoidin, a heavily sulfated polysaccharide, may interfere with the ability of leukocytes to interact with sulfate-containing proteoglycans on the surface of vascular endothelium.…”
Section: Discussionmentioning
confidence: 56%
“…An obvious candidate to explain the L-and P-selectin-independent leukocyte rolling is E-selectin, the third member of the selectin family and a glycoprotein also postulated to induce leukocyte rolling (49). It is, however, unlikely that E-selectin participates in this rolling event since the leukocyte rolling in this study was abolished by fucoidin yet fucoidin has been shown not to bind to E-selectin (18,50). Although the identity of the fucoidin-sensitive pathway remains unknown, it is conceivable that fucoidin, a heavily sulfated polysaccharide, may interfere with the ability of leukocytes to interact with sulfate-containing proteoglycans on the surface of vascular endothelium.…”
Section: Discussionmentioning
confidence: 56%
“…For example, P-selectin may bind to sialylated and nonsialylated forms of Le x/a structures. 72 Also, binding of TIM-1 (T-cell immunoglobulin and mucin domain 1), a major P-selectin ligand that controls the rolling of activated T cells, requires a1-3 fucosylation and tyrosine sulfation for efficient binding but not sialylation. 73 On a similar note, CD24, a sialoglycoprotein highly expressed in neutrophils as well as at early stages of B-cell development, does not display the sLe x epitope but does carry a HNK-1 sulfate-containing epitope and the O-glycans that are required for such binding.…”
Section: Discussionmentioning
confidence: 99%
“…Although P-selectin also binds to sLeX and sLea, it appears to recognize a wider array of oligosaccharides than E-selectin. For example, P-selectin binds the nonsialylated trisaccharides Lex and Lea (37,125,131,134) and may bind tetrasaccharides related to sLeX and sLea having sialic acid linked a2-6 instead of a2-3 (134,135), although this point is controversial (127).…”
Section: Carbohydrate Ligandsmentioning
confidence: 99%
“…Cell adhesion assays have yielded contradictory results on the relative binding activity of E-selectin for sLex and sLea ( 121,129), whereas quantitative inhibition assays using solution-phase oligosaccharides indicate that sLea binds E-selectin with a higher affinity than does sLex ( 131). In addition, two modifications of sLex and sLea that result in substantial increases in apparent binding affinities for E-selectin have been identified (131). These are the addition ofan 8-methoxycarbonyloctyl aglycone (-(CH2)8CO2CH3) attached in a ,B-glycosidic linkage to the reducing sugar, and the substitution of an amino or azido moiety for the N-acetyl group at carbon 2 ofGlcNAc.…”
Section: Carbohydrate Ligandsmentioning
confidence: 99%